Mortality and neurological outcome in the elderly after target temperature management for out-of-hospital cardiac arrest. (June 2015) - Winther-Jensen, Matilde; Pellis, Tommaso; Kuiper, Michael; Koopmans, Matty; Hassager, Christian; Nielsen, Niklas; Wetterslev, Jørn; Cronberg, Tobias; Erlinge, David; Friberg, Hans; Gasche, Yvan; Horn, Janneke; et al.
Abstract: Aim: To assess older age as a prognostic factor in patients resuscitated from out-of-hospital-cardiac arrest (OHCA) and the interaction between age and level of target temperature management. Methods and results: 950 patients included in the target temperature management (TTM) trial were randomly allocated to TTM at 33 or 36 °C for 24 h. We assessed survival and cerebral outcome (cerebral performance category, CPC and modified Rankin scale, mRS) using age as predictor, dividing patients into 5 age groups: ≤65 (median), 66–70, 71–75, 76–80 and >80 years of age. Shockable rhythm decreased with higher age groups, p = 0.001, the same was true for ST segment elevation on ECG at admission, p < 0.01. Increasing age was associated with a higher mortality rate (HR = 1.04 per year, 95% CI = 1.03–1.06, p < 0.001) after adjusting for confounders. Octogenarians had an increased mortality (HR = 3.5, CI: 2.5–5.0, p < 0.001) compared to patients ≤65 years of age. Favorable vs. unfavorable outcome measured by CPC and mRS in survivors was different between age groups with adverse outcomes more prevalent in higher age groups (CPC: p = 0.04, mRS: p = 0.001). The interaction between age and target temperature allocation was not statistically significant for either mortality or neurological outcome. Conclusion: Increasing age is associated with significantly increased mortality after OHCA, but mortality rate is not influenced by level of target temperature. Risk of poor neurological outcome also increases with age, but is not modified by level of target temperature.